Human Cloning: Who’s Concern? - Bridgewater, Ayman T.; Worden, Michael P. Worden; Wang, Fuzhou (Science Insights, 2016)
Cloning is basically a biological mechanism in which parthenogenetic reproduction employed by one or more genetically identical cells, plants or organisms are derived from one parent. The word clone is from the Greek word “klon”, meaning a twig or slip from a plant. By taking many cuttings from one parent plant, genetic replicas with identical features and functions can be developed. The recent successful cloning from an adult sheep cell has raised the possibility of using asexual means to replicate humans. Through cloning the following clinical questions might be resolved: the course of spontaneous abortions, embryogenesis, carcinogenesis, and the use of embryonic tissue for transplantation. However, reproducing humans by use of cloning has raises serious legal, religious, and social problems. There are two methods used for cloning humans namely nuclear cloning and embryo splitting. Nuclear cloning in human reproduction should be prohibited because there are no extra major benefits by its application. It can only create additional medical, ethical, and social problems. The potential of cloning by embryo splitting for minimizing clinical costs and risks as well as increasing the rate of success for couples who are infertile and having children for them is a challenge. The minor legal and religious problems can finally be settled. If policymaker’s guidelines win international acceptance and if they succeed, it may take less time to reach this goal.